2021
DOI: 10.1186/s12872-021-02227-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tp-e interval, Tp-e/QT ratio and index of cardiac-electrophysiological balance in patients with tinnitus

Abstract: Background Tinnitus is a common auditory symptom. Dysfunction in the autonomic nervous system (ANS) is an essential part of the etiopathogenesis of tinnitus. ANS regulates heart rate and heart rhythm and can lead to ventricular repolarization changes, which can cause malignant ventricular arrhythmias. T wave peak-to-end T(p-e) interval and T(p-e)/QT ratio are known ventricular arrhythmia indexes, and the index of cardiac-electrophysiological balance (iCEB) is a novel index that can be used to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…There are few studies on ICEB in the literature. ICEB value is increased in cardiac diseases such as increased pericardial volume or acute myocarditis with arrhythmia and non-cardiac diseases such as rheumatoid arthritis, tinnitus, and endstage renal disease [22][23][24][25][26]. Our study observed that the ICEB and ICEBc values were significantly high in aneurysmal SAH patients.…”
Section: Discussionsupporting
confidence: 46%
“…There are few studies on ICEB in the literature. ICEB value is increased in cardiac diseases such as increased pericardial volume or acute myocarditis with arrhythmia and non-cardiac diseases such as rheumatoid arthritis, tinnitus, and endstage renal disease [22][23][24][25][26]. Our study observed that the ICEB and ICEBc values were significantly high in aneurysmal SAH patients.…”
Section: Discussionsupporting
confidence: 46%
“…In addition, depression has been researched more intensively due to its relationship with events like sudden cardiac arrest due to malignant cardiac arrhythmia [ 32 ]. Changes in cardiac autonomic neural tone and high sympathetic activity in the ventricular myocardium are linked with total repolarization distribution and increased arrhythmia risk [ 33 ]. Cardiovascular autonomic dysfunction, sympathetic dominance, and parasympathetic withdrawal are frequently proposed mechanisms linking arrhythmia risk to psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that iCEB and iCEBc were elevated after hemodialysis (iCEB: 4.38 ± 0.76 vs. 4.02 ± 0.73, P = 0.016; iCEBc: 4.91 ± 0.73 vs. 4.42 ± 0.80, P = 0.006), but there was no significant change in the QT interval or QTc, indicating that the new ECG marker was more sensitive to cardiac electrophysiological balance ( 22 ). However, in some studies, differences in iCEB were often explained by differences in QTc or QRS duration ( 12 , 23 ). In fact, no study has directly linked iCEBc to cardiac or all-cause death.…”
Section: Discussionmentioning
confidence: 99%